Pemberdayaan Kelompok Pengrajin Tas On Iboh Guna Membentuk Produk Pesisir Berdaya Saing Tinggi Melalui Pelatihan - Musrizal, Musrizal; Mukhlis, Mukhlis; Muliari, Muliari; Yusrawati, Yusrawati; Konadi, Win (Aceh Journal of Community Engagement (AJCE), 2025)
This empowerment activity aims to increase the understanding and ability of business actors on Iboh Bags to produce high competitive coastal products. The coastal area of ​​Gampong Geudong Tampu, Jeumpa District has raw materials to produce superior products on Iboh Bags also has a hereditary woven ability. The main objective is to develop synergy between universities and business actors so that training and empowerment need to form and compile product designs and diversify products that are upto date. with of this empowerment need to train the surrounding community to make various woven using on Iboh Bags. This empowerment acivity uses demonstration and lecture methods. It is hoped that after this empowerment, high competitive products can be formed.